Effects of nematicides on nematode population densities and crop yield in a turnip-corn-pea cropping system - Johnson, A.W.; Dowler, C.C.; Glaze, N. C.; Summer, D.R.; Chalfant, R. B.; Golden, A.M.; Epperson, J.E. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1990)
Four management systems were evaluated in a six-year study to control nematodes in a turnip-corn-pea annual cropping System on plots of Tifton loamy sand naturally infested with Meloidogyne spp. (about 90 % M. incognita and 10% M. hapla), Pratylenchus spp. (about 65% P. scribneri, 25% P. brachyurus, and 10% P. zeae), Paratrichodorus minor and Criconemella ornata. Turnip (Brassica campestris subsp. rapifera) supported low numbers of all nematodes. 'Pioneer 3369A' corn (Zea mays) supported greater numbers of all nematodes than 'Funks G-4507'. Population densities of Meloidogyne spp. juveniles (J2) were suppressed below 80 per 150 cm3 of soil by 98 % methyl bromide + 2 % chloropicrin and 20 % methyl isothiocyanate + 80 % chlorinated C3 hydrocarbons on turnip and corn, and increased rapidly on 'Pinkeye purplehull', but not on a resistant cultivar, 'Worthmore' pea (Vigna unguiculata). Population densities of other nematodes were not affected by cultivar of pea or the nematicide, ethoprop. Fenamiphos was more effective than ethoprop in suppressing nematode population densities. Increases in crop yield in the intensive management system ranged from 4% to 52% over untreated controls.